Effect of silver nanoparticles in the liver of female quail (Coturnix coturnix ) - Baghdad Science Journal (مجلة بغداد للعلوم)
This study aimed to identify the alterations of liver in the quail (Coturnix coturnix) exposed by nanosilver particles.45 quail (females) were collected from agriculture research center in Abu-Ghraib, divided into (6) groups including: T1(12 quails were exposed to 4ppm), T2 (12 quails were exposed to 8ppm) and T3 (12 quails were exposed to 12ppm) of silver nanoparticles solution for 60 days. As well as three groups for control (3 females for each). Birds were dissected to isolate livers for histological preperations after fixation with Bouin's fluid, Routine stains Hematoxyline and eosin were used. Histological study showed that the structure of liver in a control groups consist of hepatocytes arranged radially cords around the central vein, Polygonal in shape with central nucleus. Sinusoid found between hepatocytes cords. The histological alterations in liver tissue included congestion of central vein, Fibrinous exudates , Infilteation of inflammatory cells, Thickness of capsule , Loss radial arrangement of hepatocytes , Incidence of fatty degeneration, Hydropic and Hyaline degeneration of hepatocytes , Appearing of councilman bodies, Pyknotic necrosis and few dilated of sinusoids in liver of group exposed to 4ppm. While the alterations in the liver with group 8ppm included occurance of precipitation of proteins near the vessels which known Amylloid , central vein dilation, An increase thickness of wall blood vessels, In addition an incidence of hemorrhage and hyaline degeneration of liver cells. Liver in group 12ppm suffer from incidence of fatty changes, Hydropic degeneration, Necrosis, Increase numbers of Concilman bodies, An incidence of giant cells, Atrophy of liver cells, Appearance of caceous necrosis and increase dilation of sinusoids and congestion.